2020
DOI: 10.3389/fmicb.2020.573588
|View full text |Cite
|
Sign up to set email alerts
|

Aquimarina sp. Associated With a Cuticular Disease of Cultured Larval Palinurid and Scyllarid Lobsters

Abstract: Shell (cuticular) disease manifests in various forms and affects many crustaceans, including lobsters. Outbreaks of white leg disease (WLD) with distinct signs of pereiopod tissue whitening and death have been observed in cultured larvae (phyllosomas) of ornate spiny lobster Panulirus ornatus , eastern rock lobster Sagmariasus verreauxi , and slipper lobster Thenus australiensis . This study aimed to characterise and identify the causative ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 61 publications
0
20
0
Order By: Relevance
“…Several OTUs did not closely affiliate with the known Aquimarina -type strains, pointing towards a wealth of likely unknown Aquimarina species yet to be cultivated. This hypothesis was further supported by the many recent reports of new Aquimarina isolates [ 4 , 16 , 18 , 21 , 38 ] and metagenome-assembled genomes (MAGs) [ 39 , 40 , 41 ], even though this genus was already described in 2005 [ 9 ]. Furthermore, an open pangenome was observed in our previous comparative genomics study, indicating that genomic redundancy was still far from being achieved [ 24 ].…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Several OTUs did not closely affiliate with the known Aquimarina -type strains, pointing towards a wealth of likely unknown Aquimarina species yet to be cultivated. This hypothesis was further supported by the many recent reports of new Aquimarina isolates [ 4 , 16 , 18 , 21 , 38 ] and metagenome-assembled genomes (MAGs) [ 39 , 40 , 41 ], even though this genus was already described in 2005 [ 9 ]. Furthermore, an open pangenome was observed in our previous comparative genomics study, indicating that genomic redundancy was still far from being achieved [ 24 ].…”
Section: Discussionmentioning
confidence: 71%
“…In the SMP dataset analyzed in this study, Aquimarina was more often identified in sediments than in the sponge samples, pointing towards a lack of preference for host-associated settings. However, it is important to consider reports of Aquimarina species as emerging pathogens of algae [ 13 , 42 ] and crustaceans [ 38 , 43 ]. In a recent metagenomics study of the octocoral microbiome, an Aquimarina OTU was enriched in necrotic octocoral tissue, suggesting it could be an indicator of dysbiosis [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Bacterial infections are commonly reported in farmed operations and can lead to high mortalities 93 . The early stages in lobster development are often the most susceptible to bacterial infections, particularly to Vibrio and Aquimarina pathogen species 92,94 …”
Section: Health and Welfare Management Of Palinurus Elephasmentioning
confidence: 99%
“…The gut microbiome plays a critical role in the overall health of the host organism. This has major implications that include impacts on growth, digestion, immune response and resistance to pathogens 94 . The core gut microbiome of P. ornatus is dominated by Tenericutes and Proteobacteria, with Vibrionaceae also being commonly found in the intestinal tract, which likely plays a role in digestion 151 .…”
Section: Health and Welfare Management Of Palinurus Elephasmentioning
confidence: 99%
See 1 more Smart Citation